Roles of Anthrax Toxin Receptor 2 in Anthrax Toxin Membrane Insertion and Pore Formation - Jianjun Sun; Pedro Jacquez (Toxins, 2016)
Interaction between bacterial toxins and cellular surface receptors is an important component of the host-pathogen interaction. Anthrax toxin protective antigen (PA) binds to the cell surface receptor, enters the cell through receptor-mediated endocytosis, and forms a pore on the endosomal membrane that translocates toxin enzymes into the cytosol of the host cell. As the major receptor for anthrax toxin in vivo, anthrax toxin receptor 2 (ANTXR2) plays an essential role in anthrax toxin action by providing the toxin with a high-affinity binding anchor on the cell membrane and a path of entry into the host cell. ANTXR2 also acts as a molecular clamp by shifting the pH threshold of PA pore formation to a more acidic pH range, which prevents premature pore formation at neutral pH before the toxin reaches the designated intracellular location. Most recent studies have suggested that the disulfide bond in the immunoglobulin (Ig)-like domain of ANTXR2 plays an essential role in anthrax toxin action. Here we will review the roles of ANTXR2 in anthrax toxin action, with an emphasis on newly updated knowledge.